Elaine : a novel - Self, Will (Grove Press, 2024)
"The Booker Prize-shortlisted author of Umbrella writes his most American novel yet-a brilliant portrait of a 1950s housewife, based on the life of the author's mother, and an exploration of sexual freedom and sublimated desire. Will Self is one of the most inimitable contemporary writers in the English language, dubbed "the most daring and delightful novelist of his generation" by The Guardian. In this brilliantly conceived new novel Self turns his forensic eye and technicolor imagination to the troubled life of his mother, Elaine. Standing by the mailbox outside 1100 Hemlock Street in Ithaca, New York, Elaine thinks of her husband and child inside her house and wonders: is this . . . it? As she begins to push back against the strictures of her life in 1950s America, she undertakes a disastrous affair that places her marriage to an Ivy League academic and former Communist Party member in peril. Based on the intimate diaries Self's mother kept for more than forty years, Elaine is a writer's attempt to reach the almost unimaginable realm: a parent's interior life prior to his own existence. Perhaps the first work of auto-oedipal fiction, Elaine shows Will Self working in an exciting new dimension, putting his stylistic talents to tremendous effect"--